Availability of medical cannabis dispensaries and cannabis abuse/dependence‐related hospitalizations in California. (10th February 2021) - Mair, Christina; Sumetsky, Natalie; Kranich, Christiana; Freisthler, Bridget
ABSTRACT: Aims: To estimate associations between both current‐ and prior‐year medical cannabis dispensary densities and hospitalizations for cannabis use disorder in California, USA between 2013 and 2016. Design: Spatial analysis of ZIP code‐level hospitalization discharge data using Bayesian Poisson hierarchical space–time models over 4 years. Setting and cases: California, USA from 2013 to 2016 (6832 space–time ZIP code units). Measurements: We assessed associations of annual hospitalizations for cannabis use disorder [assignment of a primary or secondary code for cannabis abuse and/or dependence using ICD‐9‐CM or ICD‐10‐CM (outcome)] with the total number of medical cannabis dispensaries per square mile in a ZIP code as well as dispensary temporal and spatial lags (primary exposures). Other exposure covariates included alcohol outlet densities, manual labor and retail sales densities and ZIP code‐level economic and demographic conditions. Findings: One additional dispensary per square mile was associated with a median risk ratio of 1.021 (95% credible interval 1.001, 1.041). Prior‐year dispensary density did not appear to be associated with hospitalizations (median risk ratio = 1.006, 95% CrI = 0.986, 1.026). Higher median household income, higher unemployment, greater off‐premises alcohol outlet density and lower on‐premises alcohol outlet density and poverty were all associated with decreased ZIP code‐level risk of cannabis abuse/dependence hospitalizations. Conclusions: In California, USA, the increasing density of medical cannabis dispensaries appears to be positively associated with same‐year but not next‐year hospitalizations for cannabis use disorder.